Music in the Time of COVID-19 - Consumer Behavior of the User of Streaming Services - Kšír, Otakar (2023)
This study investigates the impact of macroeconomic factors on consumer behavior in the music streaming industry. Research hypotheses focus on reduced mobility and sentiment in music due to Covid-19. Descriptive statistics reveal variation in streaming activity and a balance of happy and sad songs. Correlations show associations between residential and retail activity, and residential and workplace activity. A VAR model analyzes the relationships, suggesting potential saturation effects and mixed results on mobility's impact. Economic factors show a positive relationship with total streams, while Covid-19 variables exhibit positive coefficients. The sentiment in music is negatively impacted by cumulative deaths. The study highlights economic factors, mobility patterns, and government restrictions influencing streaming. Limitations include simplifications in measuring restrictions, suggesting further research on variables and time period extension.